Next-generation multijunction solar cells: The promise of II-VI materials - Garland, J. W.; Biegala, T.; Carmody, M.; Gilmore, C.; Sivananthan, S. (Journal of applied physics, 2011)
High concentration photovoltaic (HCPV) systems offer the highest photovoltaic (PV) conversion efficiencies. Also, as production is beginning to ramp up, HCPV is becoming cost competitive with thin-film poly-CdTe and crystalline Si systems in high solar insolation regions. High solar concentrations, X ∼500, are used to increase cell efficiencies and greatly reduce the cell area per unit of incident solar radiation, thereby greatly reducing the cell cost per watt. The monolithic three-junction (3J) solar cells presently used in HCPV systems typically consist of two epitaxial III-V homojunctions, such as GaInP and GaInAs, grown on an active Ge substrate by metal-organic chemical vapor deposition (MOCVD). The III-V bandgaps are chosen to match the currents generated in each junction and minimize the energy lost to thermalization of the electron-hole pairs generated, subject to the constraint of approximate lattice matching. We propose using cells consisting of one or more CdTe-based II-VI homojunctions grown on large-area active Si substrates by high-throughput MBE or a less expensive high-vacuum deposition technique as an alternative to III-V based multijunction cells grown by MOCVD. The bandgap of Si is more optimal than that of Ge for two-junction (2J) or 3J cells, and lattice mismatches affect the efficiencies of such cells only slightly, which allows greater freedom in the choice of bandgaps, and thus the potential for higher efficiencies. Also, such cells could be manufactured at a much lower cost due to the larger area, much lower cost and superior mechanical properties of Si substrates as compared to Ge substrates. The much lower cell cost also would enable medium concentration PV systems that would require more cell area, but with simplified, less expensive tracking and optics, resulting in lower overall system costs. Promising initial results from material-property measurements and single-junction and 2J CdZnTe/Si cell characterization results are given. Both the promise of the proposed technology and the challenges it faces are discussed.